2018
DOI: 10.1111/nan.12483
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of pattern recognition receptors in skeletal muscle of SOD1(G93A) amyotrophic lateral sclerosis (ALS) mice and sporadic ALS patients

Abstract: Our findings suggest that increased inflammasome activation may be involved in skeletal muscle pathology in ALS. Furthermore, elevated levels of NLRC4, caspase 1 and IL1β reflect early changes in the skeletal muscle and may contribute to the denervation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 127 publications
(156 reference statements)
2
20
0
Order By: Relevance
“…On the other hand, lower caspase-1 gene expression in spinal cord in non-treated SOD1G93A mice was already described by our group, which is in accordance with our results [16]. NLRP3 inflammasome is also active in the skeletal muscle, showing increased levels of caspase-1 and IL-1β in pre-symptomatic SOD1G93A mice, and in denervated muscles from these mice and ALS patients [39]. According to our results, TTC could have a role in palliating the effects of active caspase-1 in EDL, but not in SOL.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, lower caspase-1 gene expression in spinal cord in non-treated SOD1G93A mice was already described by our group, which is in accordance with our results [16]. NLRP3 inflammasome is also active in the skeletal muscle, showing increased levels of caspase-1 and IL-1β in pre-symptomatic SOD1G93A mice, and in denervated muscles from these mice and ALS patients [39]. According to our results, TTC could have a role in palliating the effects of active caspase-1 in EDL, but not in SOL.…”
Section: Discussionsupporting
confidence: 93%
“…In our view, this discrepancy between ALS and our CTB-Sap model confirms that ALS is not a cell-autonomous MN disease and that different cell types, including muscle fibers, are independently involved in the pathological processes [29,30,31], whereas the muscle modifications observed in the CTB-Sap model are produced by denervation, as no primary defects are expected to be present in muscles. So, the comparison between different animal models will provide important information about the mechanisms under evaluation.…”
Section: Discussionmentioning
confidence: 50%
“…Deficiency in caspase-1 and IL-1b, as well as treatment with the recombinant IL-1 receptor antagonist anakinra, all significantly extended the lifespan of mutant SOD1 transgenic animals (Meissner et al, 2010). Consistently, the expression of NLRP3, NLRC4, AIM2, and caspase-1 activation has been demonstrated in neural tissue of mutant SOD1 transgenic animals (Pasinelli et al, 1998;Johann et al, 2015;Gugliandolo et al, 2018), and mutant SOD1 was shown to activate caspase-1 and IL-1b in microglia (Meissner et al, 2010;Lehmann et al, 2018). Increased caspase-1 levels have also been detected in serum of ALS patients (Ił _ zecka et al, 2001), and analysis of postmortem spinal cord tissue showed increased NLRP3, ASC, caspase-1, and IL-18 expression levels, with spinal cord astrocytes identified as the main NLRP3 inflammasome-expressing cell type (Johann et al, 2015).…”
Section: Inflammasome Activation In Amyotrophic Lateral Sclerosismentioning
confidence: 74%